The Potential Roles of Astrocytes and Microglia in the Spinal Cord and Brain After Spinal Cord Injury - Fernando da Silva Fiorin; Caroline Cunha do Espírito Santo (Neuroglia)
Background/Objectives: Spinal cord injury (SCI) is a devastating condition that leads to a cascade of cellular and molecular events, resulting in both primary and secondary damage. Among the many cells involved in the post-SCI environment, glial cells in the spinal cord and brain are pivotal in determining the trajectory of injury and repair. Methods: While recent SCI studies have shown changes in the genotype of glial cells following injury, exactly how these alterations occur after damage remains unknown. In this sense, the systemic inflammatory molecules could be involved in the connection between the spinal cord and brain, inducing glial activation by different signaling pathways. Preclinical studies have shown that nuclear factor-κB (NF-κB), Janus kinase/signal transducer and activator of transcription (JAK/STAT), and phosphoinositide 3-kinase/Akt (PI3K/Akt) signaling pathways are involved in the change in glial type. Results: These cells, which include astrocytes and microglia, exhibit dynamic responses following spinal injury, contributing to both neuroprotection and neurodegeneration. These different effects indicate that the molecular environment causes changes in the type of astrocytes and microglia, leading to different actions. Conclusions: Understanding the mechanisms of glial cell activation, it is possible to clarify the roles of these glial cells in pathophysiology and their potential repair mechanisms post-injury.